Aula Invertida como metodología para la enseñanza de la Unidad 4 de Historia de Primero BGU - Aldás Núñez, Lizbeth Estefanía (2025)
Present-day education faces more demands and challenges, necessitating modifications in the classroom through innovative approaches that go beyond traditional practices and encourage student participation and reflection. The objective of this research is to design a methodological guide for the implementation of flipped classroom, focused on strengthening the teaching-learning process of History, in Unit 4 of First BGU at Educational Unit “El Oro”. A mixed approach was used, combining qualitative and quantitative methods. The study is framed in descriptive and explanatory research, with a case report type design. For data collection, a survey was administered to 24 first-year BGU students, classroom observation sheets and an interview with the history teacher. According to the results, History teaching is based on traditional methods, which limit pedagogical diversity. Positive aspects were identified, such as the willingness of students to adopt innovative approaches. Among the negative aspects, the lack of interest and motivation of students in class was highlighted, as well as the predominance of traditional evaluations. The research concludes that the implementation of flipped classroom, together with effective feedback and the use of technological resources, can promote more dynamic and participatory learning. The methodological guide proposes adjustments in pedagogical planning and in the selection of didactic materials to enrich the teaching process, making it more attractive, meaningful and aligned with the specific needs of students in this educational context